EXPOSURE TRANSLASI AKUNTANSI PERKEMBANGAN DAN DAMPAKNYA BAGI NEGARA-NEGARA ASIA - Fitri Ella Fauziah; Murharsito Murharsito (Jurnal Dinamika Ekonomi & Bisnis, 2005)
AbstractThispresent t1111e of eco110111ic con/111011 iss1g111ng by increasing number of the multinational corporation. The corporation that their operations reach many countries  across the country border. This fact 11ot 011/y happe11ed in the industrial country, blit 110.,.,.adays there are some multinational that come from growth colintry. That reality has several impacts, 01.e of them 1.s what usually call tlte tra11slatio11 exposure, it also known as accounting exposure. The translat1011 exposure means the exposure tlwt rise because of the translation of the foreign currency in to the home currency of rite corporatio11 in the balance sheet. Because of tlte change of the eco11on11c sit11atio11 in the world, the translation exposure problem and regulacy m many countries clla11gi11g too. And the recem re.i:11latio11 of the American government abow translation exposure that calls FASB 52 discussed in this paper. And related to the Asian mo11ewry cri.tis, w/11ch has near con11ect1011 with exposure translation, the wisdom of the Asian government about this issue provided too. This essay will try to make a simple explanation about the exposure translation that is so 1111porta111 to the economic srndies, which always threat him asfast as the clia11g111g of tlte world situation. Key words :translation e.\posure, asia11 country